Substitusi Tepung Bekatul Beras Merah Terhadap Kadar Protein dan Tingkat Kekerasan Biskuit - Yunani, Tri Tenis, Eni Purwani, S.Si., M.Si, Dwi Sarbini. SST.,Mkes (2017)
Biscuit is a popular snack consumed by many people. Raw materials of biscuits are wheat flour, which can be substituted with brown rice bran flour. Brown rice bran flour has a high fiber content and protein levels, which can be processed into biscuit with high fiber and protein. The objective of the research was to know the effect of subtitution of brown rice bran flour towards protein and hardness levels of biscuit. Designed research used was a completely random design with 4 treatments of brown rice bran flour substitution, that was 0%, 5%, 7,5%, and 10%. Data were analyzed using statistic test of Kruskal-Wallis. The result of the research showed that the highest of protein level of biscuit was revealed by substitution of 10%. The highest of hardness level of biscuit was displayed by substitution of 7,5%. Kruskal-Wallis test indicated there were no effect of brown rice bran flour substitution on protein and hardness levels of biscuit with value of p = 0,083 and p = 0,229, respectively. Keywords: Biscuit, brown rice bran flour, protein, hardness